Analysis of Camellia sinensis tea functionalities (Research, Society and Development, 2021)
Green tea produced by Camellia sinensis has become an extremely popular product in Brazil in the last decade, due to the reputation of contributing to weight loss and body fat. However, green tea may have health benefits beyond weight loss. Thus, this study aimed to expose the main functionalities of (green tea) C. sinensis, both in vitro and in vivo. To achieve the proposed objective, an exploratory bibliographic research was carried out, through investigations in scientific documents published in the literature available on Scielo, Pubmed and university repository platforms. It was observed then that green tea presents functionalities against weight loss, antioxidant action, contributes to the improvement of heart disease, cancer, diabetes, antibacterial and antiviral action. Regarding contraindications, they were not identified, however the excess of green tea can cause irritation in the stomach of some people, moreover, overdosing with tea would be practically impossible. It is necessary to carry out more studies in order to further identify the functionalities of green tea from C. sinensis for the population and patients in specific treatments and in fact prove its effectiveness, ensuring more safety in prescriptions and indications to patients.